Search for light sterile neutrinos with two neutrino beams at MicroBooNE - P. Abratenko; D. Andrade Aldana; L. Arellano; J. Asaadi; A. Ashkenazi; S. Balasubramanian; B. Baller; A. Barnard; G. Barr; D. Barrow; J. Barrow; V. Basque; et al. (Nature, 2025)
Abstract The existence of three distinct neutrino flavours, ν e , ν μ and ν τ , is a central tenet of the Standard Model of particle physics 1,2 . Quantum-mechanical interference can allow a neutrino of one initial flavour to be detected sometime later as a different flavour, a process called neutrino oscillation. Several anomalous observations inconsistent with this three-flavour picture have motivated the hypothesis that an additional neutrino state exists, which does not interact directly with matter, termed as ‘sterile’ neutrino, ν s (refs. 3–9 ). This includes anomalous observations from the Liquid Scintillator Neutrino Detector (LSND) 3 experiment and Mini-Booster Neutrino Experiment (MiniBooNE) 4,5 , consistent with ν μ → ν e transitions at a distance inconsistent with the three-neutrino picture. Here we use data obtained from the MicroBooNE liquid-argon time projection chamber 10 in two accelerator neutrino beams to exclude the single light sterile neutrino interpretation of the LSND and MiniBooNE anomalies at the 95% confidence level (CL). Moreover, we rule out a notable portion of the parameter space that could explain the gallium anomaly 6–8 . This is one of the first measurements to use two accelerator neutrino beams to break a degeneracy between ν e appearance and disappearance, which would otherwise weaken the sensitivity to the sterile neutrino hypothesis. We find no evidence for either ν μ → ν e flavour transitions or ν e disappearance that would indicate non-standard flavour oscillations. Our results indicate that previous anomalous observations consistent with ν μ → ν e transitions cannot be explained by introducing a single sterile neutrino state.